Role of Lung Scan for Detection of Pneumothorax in Operation Theatre - Poudel, S.C.; Rayamajhi, A.J.; Bhattarai, P.R.; Yadav, R.K. (Birat Journal of Health Sciences, 2017)
Iatrogenic pneumothorax is life threatening complication that an anesthesiologist may encounter in operating room while performing various procedure such as central venous catheterization brachial plexus block paravertebral block or during surgery like pyelolithotomy, laparoscopic cholecystectomy, percutaneous nephrolithotomy. Ultrasound can be the diagnostic tool for prompt diagnosis and managementof these situations. As there is overwhelm use of ultrasound in emergency department and ICU setting, by understanding few ultrasonic terms like lines, modes, signs and points of lung scan it can be easily utilized in operation room. Likewise, lung ultrasounds in emergency (BLUE) and fluid administration by lung ultrasound (FALL) are recently being recommending to be used in emergency and ICU. We report two cases where lung scan was beneficial for management of pneumothorax in our operation theater. Birat Journal of Health Sciences 2016 1(1): 75-77